The Perception of Tone and Focus in Mandarin by Indonesian Learners: A Case Study - Hana Nurul Hasanah (Center of Language and Cultural Studies [CLCS], 2019)
In a tone language, the interface between tone, intonation, and focus will affect the pitch height and contour of tones. Previous perceptual studies revealed the potential conflicts in perceiving pitch variations at lexical and post-lexical levels that were experienced by either native listeners or listeners who speak Mandarin language as a second or foreign language. Rarely we find research in Indonesia that provides evidence for Mandarin language learners’ perceptual ability at a post-lexical level. This paper investigated how well learners with distinct first language (L1) background identify tones that are affected by the realization of focus and the presence and location of focus in distinct intonation types. Perceptual experiments were conducted towards two groups of listeners: Mandarin learners with Indonesian L1 and learners with a tone language L1 background (Hakka or Hokkien). Their identification accuracy (IA) rate in recognizing the tone type for the last syllable with a narrow focus was compared with their IA in identifying the location of the focus. In general, identifying tone type was easier than identifying focus position for both groups. However, the Mean from each group showed that learners with a tone language L1 were slightly better than the other group. Results exhibited more similarities between the two groups of the listener, which indicates that L1 background only has a mild effect on the perceptual ability of Indonesian learners of Mandarin as a foreign language.